Effect of problem-based learning strategy on the learning outcomes of senior secondary school students in Mathematics - Akorede Ayoola Asanre; Aviwe Sondlo; Abiodun Taiwo Oluwadayo (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: Problem-based learning (PBL) has been identified as an effective instructional strategy, particularly in enhancing student outcomes in various subjects, including mathematics. However, its impact on senior secondary school students' mathematics achievement and attitudes in Ogun State, Nigeria, remains underexplored.Aims: This study aims to investigate the effects of PBL on the mathematics achievement and attitudes of senior secondary school students in the Ijebu Ode area of Ogun State, Nigeria. Additionally, it examines the influence of gender on students' attitudes towards mathematics.Method: A sample of 100 students was randomly selected from two senior secondary schools, divided into an experimental group and a control group. The experimental group received instruction through PBL, while the control group followed traditional teaching methods. Six hypotheses were tested at a significance level of 0.05. Data were collected using a teaching guide on PBL, the Mathematics Achievement Test (MAT), and the Mathematics Attitude Scale, with reliabilities of 0.82 and 0.88, respectively. Analysis of Covariance (ANCOVA) was used to analyze the data.Results: The findings revealed a significant positive effect of PBL on both the achievement and attitudes towards mathematics among the senior secondary school students. Additionally, gender was found to significantly influence students' attitudes towards mathematics.Conclusion: The study concludes that PBL significantly enhances both mathematics achievement and attitudes among senior secondary school students in Ijebu Ode, Ogun State, Nigeria. It recommends that schools integrate student-centered teaching methods, including PBL, into their curricula and encourage teachers to adopt these strategies.